The Effect of Peer Tutor Model on Antenatal Care Skill Competencies in Learning Laboratory Skills for Students of Langsa Midwifery Study Program - Harahap, Meliani Sukmadewi; Alchalidi, Alchalidi; Baharuddin, Baharuddin; Ramli, Nurlaili (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Peer-assisted learning is a student-centered learning method that involves discussions between friends or seniors as teachers and participants as being taught. Realize optimal education; it is necessary to choose the peer tutorial method to increase antenatal care (ANC) skills in laboratory skills. AIM: This study aims to determine the effect of the learning peer tutor model for laboratory skills on the competence of ANC skills in the Langsa Midwifery Study Program’s first-level students. METHODS: This study used a pre-experimental approach with a one-group pretest-posttest design without a control group. The population used in this study were all Level I Midwifery Students of Langsa City who occupied the 2nd semester. This study’s sample was taken by purposive sampling as many as 45 respondents – data analysis using bivariate analysis. RESULTS: The results showed an effect of the peer tutor method on ANC skills’ competence before and after learning laboratory skills as evidenced by a statistical test with a value (p < 0.05), namely, 0.047 < 0.05. The results also showed differences in students’ competence before and after the peer tutoring method was carried out in laboratory skills learning, as evidenced by the results of statistical tests with p < 0.05, namely, 0.000 < 0.05. Peer tutor method learning effectively increases ANC skill competencies in learning laboratory skills for midwifery study students. CONCLUSION: Peer tutor model effective in improving ANC skills competency in skill learning for midwifery study students.